Upah Minimum, Skala Upah dan Produktifitas Kerja - Tuwinanto Tuwinanto; Dedi Rianto Rahadi (Universitas Pendidikan Nasional, 2021)
The minimum wage in Indonesia is one that is often discussed in the industrial world, this is because there are still some companies that implement a wage system that does not include a wage scale instrument, one of which is the period of work. So that it causes disharmony between old workers and new workers and can make internal communication not run smoothly.